Myocardial deformation as a predictor of right ventricular pacing‐induced cardiomyopathy in the pediatric population. (16th December 2019) - Dasgupta, Soham; Madani, Rohit; Figueroa, Janet; Cox, David; Ferguson, Eric; Border, William; Sachdeva, Ritu; Fischbach, Peter; Whitehill, Robert
Abstract: Introduction: Right ventricular pacing is associated with pacemaker induced cardiomyopathy and lesser degrees of pacing‐induced LV dysfunction (PIVD) manifested by a reduction in left ventricular ejection fraction (LVEF). Our objective was to determine whether apical 4 chamber strain (A4C) by echocardiography can identify patients at risk of PIVD before LVEF declines. Methods and Results: A retrospective chart review of patients (0‐21 years) who had a pacemaker with a ventricular lead placed between 2011 and 2017 was performed. Patients were divided into group A (LVEF <55% and/or >10% decline in LVEF within 12 months of pacemaker placement) and group B. Data have collected before and 1 and 12 months postpacemaker implantation. There were 30 patients in the group A and 60 in group B. At 1 and 12 months postpacemaker implantation, the LVEF was significantly lower while the A4C and QRS duration on electrocardiogram were significantly higher in the group A. While the LVEF and A4C became markedly abnormal in group A as early as 1 month, the A4C did not seem to demonstrate such marked abnormalities in group B. However, a sub‐analysis of patients in the group A with preserved LVEF at 1 month demonstrated significant worsening in their A4C at that time. Conclusion: Myocardial deformation imaging may be a clinically useful tool for the prediction of a decline in LV systolic function following pacemaker implantation. Abnormalities in A4C seem to appear before LVEF decline and as soon as 1‐month postpacemaker implantation.